Word-Representability of Graphs via Split Decomposition - Dwary, Tithi (My University, 2026)
The theory of word-representable graphs lies at the intersection of graph theory and combinatorics on words. This thesis uses a graph decomposition technique, viz., split decomposition, to study the theory of word representable graphs. Further, the thesis constructs minimum-word-representants for certain classes of graphs.
krishna, K V